2006
DOI: 10.1038/sj.gene.6364287
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the type I interferon gene cluster on 9p21 influences susceptibility to asthma and atopy

Abstract: A genome-wide screen for asthma and atopy susceptibility alleles conducted in the Hutterites, a founder population of European descent, reported evidence of linkage with a short tandem repeat polymorphism (STRP) within the type I interferon (IFN) gene cluster on chromosome 9p21. The goal of this study was to identify variation within the IFN gene cluster that influences susceptibility to asthma and atopic phenotypes. We screened approximately 25 kb of sequence, including the flanking sequence of all 15 functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Moreover, clinical symptoms of asthma can be controlled using low doses of recombinant IFN-α (Gratzl et al, 2000). Genetic association studies have also identified several risk factors for asthma in the type I IFN system, such as variants of IFNA, IFNB and TLR gene super-families (Chan et al, 2006;Yang et al, 2006). Together with the observations in this study, we can postulate that nonatopic asthma and autoimmune disorders are closely related, and they may well be two opposite outcomes downstream of a common pathway, in which IRF5 as well as the type I IFN system are involved.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, clinical symptoms of asthma can be controlled using low doses of recombinant IFN-α (Gratzl et al, 2000). Genetic association studies have also identified several risk factors for asthma in the type I IFN system, such as variants of IFNA, IFNB and TLR gene super-families (Chan et al, 2006;Yang et al, 2006). Together with the observations in this study, we can postulate that nonatopic asthma and autoimmune disorders are closely related, and they may well be two opposite outcomes downstream of a common pathway, in which IRF5 as well as the type I IFN system are involved.…”
Section: Discussionmentioning
confidence: 98%
“…Gene-gene interaction between IL-4 and IL-4R␣ and asthma has been demonstrated in several populations (25,26). Because no significant or moderately significant associations were found for IL-4 SNPs in our population, we did not test for interaction between this gene and IL-4R␣.…”
Section: Discussionmentioning
confidence: 99%
“…This regulatory mechanism might be crucial for differential IFN-A gene expression and therefore might determine the amplitude of immune responses dependent on IFN-␣ subtypes that differ by their relative potencies (16,22,84). By restraining the expression of various IFN-␣ subtypes, this control level might also be an absolute requirement for the organism to maintain regulated IFN-␣ production and to prevent immunemediated and autoimmune diseases (6,81).…”
Section: Discussionmentioning
confidence: 99%